2023
DOI: 10.1093/ehjci/jead032
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of relative apical sparing in aortic stenosis: insights from an echo and cardiovascular magnetic resonance study of patients referred for surgical aortic valve replacement

Abstract: Aims This study aims to assess the prevalence of relative apical sparing pattern (RASP) in patients with severe symptomatic aortic stenosis (AS), referred for surgical aortic valve replacement (AVR), to evaluate its significance, possible relation to amyloid deposition, and persistence after surgery. Methods and results Prospective study of 150 consecutive patients [age 73 (interquartile range: 68–77), 51% women], with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Echocardiography also demonstrates a longitudinal strain pattern in ATTR cardiomyopathy characterized by normal or near-normal longitudinal strain values in the apical LV segments and reduced strain values in the basal LV segments . These strain abnormalities have been observed in other diseases, such as aortic stenosis, and are not specific for ATTR …”
Section: Discussionmentioning
confidence: 90%
“…Echocardiography also demonstrates a longitudinal strain pattern in ATTR cardiomyopathy characterized by normal or near-normal longitudinal strain values in the apical LV segments and reduced strain values in the basal LV segments . These strain abnormalities have been observed in other diseases, such as aortic stenosis, and are not specific for ATTR …”
Section: Discussionmentioning
confidence: 90%
“…In another study the relative apical sparing criterion was present in much more (88%) patients with severe aortic valve stenosis before transcatheter aortic valve implantation (TAVI) and after TAVI it was found in only 77% of the patients 15 . The latter two studies 18,19 showed that the presence of relative apical sparing was associated with more severe aortic valve disease, left ventricular dysfunction and hypertrophy, which was in some or most cases reversible after aortic valve replacement.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of relative apical sparing was also reported in patients with primary hyperoxaluria type 1, a hereditary cause of progressive nephrocalcinosis, that commonly leads to end‐stage renal failure due to relatively lower accumulation of oxalate crystals in the apex compared with the basal and mid segments 17 . The relative apical sparing criterion was present in 15.3% of patients with severe, symptomatic valvular aortic stenosis in whom CA was ruled out by histological examination, and proved to be mostly (in 91% of cases) reversible after aortic valve replacement surgery 18 . In another study the relative apical sparing criterion was present in much more (88%) patients with severe aortic valve stenosis before transcatheter aortic valve implantation (TAVI) and after TAVI it was found in only 77% of the patients 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Proposed echocardiographic scores are time intensive and still fail to reach a sensitivity of more than 61% (for indication of further tests) and 46% (for diagnosis of CA). 9,10 Hence, we need more precise and cost-effective screening tools to preselect AS patients for further CA testing. Here, proteomic biomarkers may yield valuable additional information.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Apical sparing-a suggested marker for CAalso does not seem to be typical of CA in AS. 9 Suggested echocardiographic scores show subpar sensitivity despite elaborate diastolic characterization. 10 Therefore, the preselection of AS patients for further CA screening remains difficult.…”
Section: Introductionmentioning
confidence: 99%